(untitled) (Journal of Bio-Science, 2021)
The present study is illustrated complete morphometric and meristic characteristics of fresh water fish, walking snakehead, Channa orientalis (Bloch & Schneider 1801), using nine linear dimensions and covering different fin-rays (i.e., dorsal fin, D; pectoral fin, P1; pelvic fin, P2; anal fin, A and caudal fin,C) from the wetland ecosystem Gajnar Beel in northwestern (NW) Bangladesh. Total 230 specimens of C. orientalis were collected from the Gajnar Beel in the time of January to December 2018 by several local fishing gears (e.g., cast net, gill net and square lift net (mesh size ranges: 1.5 - 2.5 cm, 1.5 - 2.0 cm, & 2.0 cm, respectively). Different morphometric lengths were measured to 0.01 cm, and whole body weight (BW) was estimated 0.01 g for each individual. Fin rays and scales (including lateral line scale) were computed by a magnifying glass. All LWRs were highly significant (p<0.0001) with the r2 values ≥0.978. Based on r2 value, LWR by BW vs. TL was the best fitted model among nine equations. However, the LLRs were also significant with r2 values ≥0.992. According to r2 value, LLR by TL vs. SL (TL = a + b × SL) shown the best fitted model among eight equations. The fin formula of C. orientalis is: dorsal: D. 29-35; Pectoral, P1. 12-14; Pelvic, P2. 5-6; Anal, A. 20-22; Caudal, C. 12-14. A double lateral line is present which continued with 12-13 scales in the first line and 26-28 scales in other line. The present study will be helpful for the species identification and resource management of C. orientalis in the Gajner Beel NW Bangladesh and other sub-tropical countries. J. Bio-Sci. 29(2): 53-60, 2021 (December)